Academic burnout in Peruvian university students - Estrada Araoz, Edwin Gustavo (2021)
The present research aimed to describe the academic burnout of the students of the professional education career of a public university in Madre de Dios (Peru). The research approach was quantitative, the design was non-experimental, and the type was descriptive-transectional. The sample consisted of 220 students to whom a sociodemographic and academic data questionnaire was applied as well as the Maslach Burnout Inventory Student Survey (MBI-SS), an instrument with adequate levels of validity and reliability. The findings indicate that students are characterized by moderate levels of academic burnout and it was determined that some variables such as sex, age group, work situation and year of study are significantly associated with academic burnout. Finally, it was concluded that it is necessary to design and implement programs that develop the protective factors of students so that they can adequately cope with adverse and stressful situations and thus decrease the prevalence of academic burnout.